2014
DOI: 10.1002/mbo3.151
|View full text |Cite
|
Sign up to set email alerts
|

Acid Resistance in Francisella tularensis

Abstract: Francisella tularensis, the etiologic agent of tularemia, can survive under acidic conditions. Tularemia can be acquired by several routes, including by ingestion of contaminated food or water. While acid resistance is usually associated with a low oral infective dose (ID), the ID for gastrointestinal illness is quite high. In this study, four strains of F. tularensis ssp. tularensis (type A) and four strains of F. tularensis ssp. holarctica (type B) were examined for innate acid resistance and the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…While ClcA and ClcB in E. coli are believed to have different pH optima (Chris Miller, personal correspondence), there is no redundant gene in Francisella . Several F. tularensis type B strains, including OR96‐0246, were previously examined for gastric acid resistance, but may not appropriately reflect conditions during a macrophage infection (Adcock et al, 2014 ). Furthermore, while reductions in viability were observed for cultures exposed to SGF (synthetic gastric fluid, pH 2.5 and 4.0) compared to acidic PBS (pH 2.5), survival was nonetheless higher for WT strains than for attenuated strains such as LVS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While ClcA and ClcB in E. coli are believed to have different pH optima (Chris Miller, personal correspondence), there is no redundant gene in Francisella . Several F. tularensis type B strains, including OR96‐0246, were previously examined for gastric acid resistance, but may not appropriately reflect conditions during a macrophage infection (Adcock et al, 2014 ). Furthermore, while reductions in viability were observed for cultures exposed to SGF (synthetic gastric fluid, pH 2.5 and 4.0) compared to acidic PBS (pH 2.5), survival was nonetheless higher for WT strains than for attenuated strains such as LVS.…”
Section: Resultsmentioning
confidence: 99%
“…Brown et al monitored serum from North American cottontail rabbits infected with type B strains OR96‐0246 and KY99‐3387 and reported a strong humoral response in rabbits that survived the past 14 days (Brown et al, 2015 ). Many studies of virulent type B strains typically focus on clinical or diagnostic aspects of tularemia but lack mechanistic insights (Adcock et al, 2014 ; Fritzsch & Splettstoesser, 2010 ; Johansson et al, 2000 , 2014 ; Stenmark et al, 2003 ; Versage et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…tularensis and F. tularensis subsp. holarctica show relatively high survival following temporal acid treatment ( 37 , 38 ), and low-nutrient preadaptation in natural water resulted in even greater acid resistance ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the least favorable condition of 5°C and pH 8.0, a mean C × T of 76.1 mg‐min/L was required to achieve a 4 log 10 level of inactivation. F. tularensis was more resistant to inactivation by free chlorine than other vegetative bacterial biothreat agents and other waterborne bacterial pathogens (Rose & Rice 2014).…”
Section: Treatment Studiesmentioning
confidence: 99%
“…The 50% infective dose (the dose required for 50% infectivity) required for gastrointestinal infection in humans has been reported to be 10 8 colony-forming units (cfu) (Hornick et al 1966). The organism exhibits a degree of innate acid resistance (Humrighouse et al 2011), but laboratory studies have found that the bacterium is susceptible to conditions that would normally be encountered in the human stomach (Adcock et al 2014). Gastrointestinal symptoms can sometimes also result from tularemia acquired by means other than ingestion, such as arthropod bites-e.g., ticks (Zaidi & Singer 2002).…”
Section: The Diseasementioning
confidence: 99%